An Investigation of the Effects of Some Parameters on the Shooting Performance of Air Rifle Shooters in Terms of Gender and Level of Competition - İbrahim Can; Ceren Ertürk; Serdar Bayrakdaroğlu (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to compare the effects of some parameters on the shooting performance of air rifle shootersin terms of gender and level of competition. To achieve this, 20 air rifle shooters who ranked in the Air Guns Turkey Cup and Air Guns Turkey Championships volunteered for the study. In this study, the height and body composition of the participants were measured, and then grip strength, back and leg strength, heart rate, flexibility, vital capacity, static balance, dynamic balance, and reaction time tests were performed. One (1) series, which included ten (10) shots was fired to determine the shooting success of the participants. There found a positive and high statistical significance between the scoresof the elite shooters in a series of shots and their expected vital capacity measurements (r=.656; p lt;0.05), between the scores of the junior shooters in a series of shots, their measured vital capacity (r=.820; p lt;0.01), their vital capacity percentage (r=.686; p lt;0.05), and their right-hand grip strength (r=.703; p lt;0.05). Furthermore, while a negative and high significance was acquired between the male participants’ scores in a series of shotsand the right foot dynamic balance (r= -790; p lt;0.05), there was a positive and high correlation between the scores of female participants in a series of shots and their expected vital capacity (r=.704; p lt;0.05). As a result, it was concluded that some performance parameters in terms of gender and level of competition affected the shooting performance of the participants.